IrrigaÇão por gotejo na maturaÇão e classificaÇão do café - De Paiva Custódio, Anselmo Augusto [UNESP]; De Faria, Manoel Alves; Rezende, Fátima Conceição; Augusto De Paiva Custódio, Adriano; Natalino Martins Gomes, E. (My University, 2014)
The objective of this study was to evaluate maturation and classification of coffee beans under drip irrigation using different management in three harvests after pruning. Coffee plants of Acaiá MG-1474 cultivar were irrigated since planting in 1997 and pruned in 2004. The experimental design was randomized blocks with five treatments and four replications. The treatments consisted of different strategies for irrigation management: A = no irrigation (control); B = irrigation all over the year whenever the water content available in the soil (WCAS) reached 25% of total water availability (TWA) in the 0-40 cm layer; C= irrigation all over the year whenever WCAS <75% TWA in the 0-40 cm layer; D= irrigation all over the year whenever WCAS <75% TWA in January, February, March, July, October, November and December; and whenever WCAS <25% TWA in April, May, June, August and September in the 0-40 cm layer; E= irrigation in April, May, June, August and September when WCAS <75% TWA in the 0-40 cm layer. The E irrigation management was the most suitable as it consumes less water and remains in the group with the highest percentage of grains with sieves 16 and above, and the lowest percentage of intrinsic defects. The major defects were found in the green, burnt grains and in those with bad fillings.
Drip irrigation during maturation and classification of coffee beans
Keywords: Coffea Arabica Lineu; Defects; Drip; Sieves; Yield